(untitled) (SETARA : Jurnal Ilmu Hukum, 2025)
This article examines how Presidential Regulation Number 46 of 2025 should be harmonized with the earlier public procurement framework so that legal certainty for procurement officials and business actors can be preserved during the 2025 transition period. The issue arises because Presidential Regulation Number 16 of 2018 has been amended by Presidential Regulation Number 12 of 2021 and again by Presidential Regulation Number 46 of 2025, while the National Public Procurement Agency also issued Circular Letter Number 1 of 2025 to explain transitional implementation. Using normative legal research with statutory and conceptual approaches, this article maps the amendment chain, identifies the legal points that require synchronization with implementation guidelines and contract documents, and formulates a harmonization framework grounded in official legal sources.